Pre-protest restrictions (Iran) - Voidly (2022)
CRITICAL severity censorship detected in Iran. Confidence: 95%. Data sourced from OONI.
Censorship Incident ID: IR-2022-0002
Keywords: censorship; IR; censorship; critical